Standarisasi Biaya Produksi Terhadap Total Quality Control PAda PTP. Pabrik Gula Takalar - Jamaluddin Jamaluddin (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
In planning the profit, understanding the relationship between the cost of profit, volume and profit are fundamental in its analysis. This study examines the standardization of the production costs of the company to increase quality control of PTP. Pabrik Gula Takalar. The results concluded that the cost of production on PTP. Sugar Factory Takalar can improve the expected of quality control. In addition, production quality control system implemented in the sugar processing is not been applied to the Statistical Quality Control.